Language Learning Environments: Comparing Online and Traditional Language Teaching Settings (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This paper examines the differences and similarities between online and traditional language teaching environments. The study explores the effectiveness, accessibility, and learner engagement in both settings, considering technological advancements and pedagogical strategies. By comparing these two environments, the research aims to identify the benefits and challenges associated with each, providing insights into how they can be optimized to enhance language acquisition. The study also discusses the impact of the COVID-19 pandemic on the adoption and adaptation of online language learning.